Vestibular assessment and management in adults: South African audiologists' expressed level of confidence and knowledge explored. (2nd January 2020) - Khoza-Shangase, Katijah; Sebothoma, Ben; Seedat, Tasneem
Abstract: Background: Vestibular assessment and management is within the scope of practice of audiology, and therefore audiologists are expected and required to assess and manage patients with vestibular disorders. Due to the developing nature of South Africa and the developing nature of audiology as a profession in the country, paucity of evidence-base regarding audiologists' training and practice confidence in this field exists. Objective : To explore South African audiologists' level of confidence and training in performing vestibular assessment and management. Methods: A survey research methodology with a cross-sectional research design was adopted, where a 29 item web-based survey was used to survey 32 audiologists from across the country. All audiologists surveyed were qualified and registered with the Health Professions Council of South Africa (HPCSA) independent practitioners. Data were analyzed using descriptive statistics. Results: Just over half of the participants (53.6%) conducting vestibular assessments in their practices. More than half (65.6%) of the audiologists received formal education from the university; while only 40.6% received clinical training. 59.4% of the participants were not confident in performing vestibular assessment; while 65.5% of participants were not confident in performing vestibular management. Over 80% of audiologists who were not confident in performing vestibular assessment and management work in public hospitals where over 70% of the South African population accesses health care. Conclusion: More audiologists are not confident in performing vestibular assessment and management, particularly those who are working in public hospitals. The findings raise implications for training and resource planning and allocation.